THE INFLUENCE OF RESPONSIVENESS OF BUSINESS LICENSE PROCESSING SERVICES ON BUSINESS ACTORS SATISFACTION AT THE NIAS REGENCY ONE-STOP INVESTMENT AND INTEGRATED SERVICE OFFICE - Hura, Medlin Anggreyni; Sihombing, Tunggul; Siahaan, Asima Yanti S (DIA: Jurnal Administrasi Publik, 2025)
Risk-based business licensing services are an important component in supporting regional economic growth. The quality of responsive services plays an important role in determining the satisfaction of business actors as service users. However, in Nias Regency, the quality of business license services still faces challenges that affect business actor satisfaction. This research uses quantitative methods, and data is collected through questionnaires distributed to 95 business actors who have processed risk-based business licenses in Nias Regency. The analysis method used in the study is SEM (Structural Equation Model) analysis. The data obtained is then analyzed and processed by conducting inferential statistical data analysis measured using SmartPLS (Partial Least Square) software, including model measurement (outer model), which aims to measure the validity and reliability of research instruments, and model structure (inner model) to describe the relationship between latent variables. The results showed that responsiveness in licensing services has a significant impact on business actor satisfaction. Responsiveness has an effect of 80.9% on business actor satisfaction, while the remaining 19.1% is the influence of other variables not examined in this study.